If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -133 + -9x = 10x + 20 Reorder the terms: -133 + -9x = 20 + 10x Solving -133 + -9x = 20 + 10x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-10x' to each side of the equation. -133 + -9x + -10x = 20 + 10x + -10x Combine like terms: -9x + -10x = -19x -133 + -19x = 20 + 10x + -10x Combine like terms: 10x + -10x = 0 -133 + -19x = 20 + 0 -133 + -19x = 20 Add '133' to each side of the equation. -133 + 133 + -19x = 20 + 133 Combine like terms: -133 + 133 = 0 0 + -19x = 20 + 133 -19x = 20 + 133 Combine like terms: 20 + 133 = 153 -19x = 153 Divide each side by '-19'. x = -8.052631579 Simplifying x = -8.052631579
| -2(5+3)+7(3-2*5)= | | 35=5-6t | | 5x+x-4/7=-4 | | B=9/8(j-39) | | z^2-z+1+i=0 | | 2=1-2n+5 | | 5x+38=40+4x | | 7x+3(x-6)=72 | | -0.5x+1.5=2.5x+2 | | X^3-18x^2-63x=0 | | 2(2x-8)=4(x-8) | | 6m+m-4(-2m+1-m)when=-8 | | 0.5x+0.25=x+0.5 | | 0.5x+0.5=2.5x+3 | | 4(x-3)=3x-2x+3 | | 1/2*(X-4) | | m^2-32m+c= | | -6=-5+-5+4 | | X+1+2X=47-2X | | -5-5x=9-9x | | x+h=r | | -0.5x+1=3x+3.5 | | 8x-5,6=0 | | 2x=90*5 | | 9x^2+11x-4=0 | | 3/4x-4(4)=20 | | Y=X+3z | | 5Y+10=60 | | 4x^3-3x-8=0 | | 39x+21=6(6x+5)+3x-9 | | y^2+20y+c= | | 4=24x-1 |